Alternating Current Electrospinning of Polycaprolactone/Chitosan Nanofibers for Wound Healing Applications - Andrade Del Olmo, Jon; Mikeš, Petr; Asatiani, Nikifor; Alonso, José María; Sáez Martínez, Virginia; Pérez González, Raúl (Polymers, 2024)
Traditional wound dressings have not been able to satisfy the needs of the regenerative medicine biomedical area. With the aim of improving tissue regeneration, nanofiber-based wound dressings fabricated by electrospinning (ES) processes have emerged as a powerful approach. Nowadays, nanofiber-based bioactive dressings are mainly developed with a combination of natural and synthetic polymers, such as polycaprolactone (PCL) and chitosan (CHI). Accordingly, herein, PCL/CHI nanofibers have been developed with varying PCL:CHI weight ratios (9:1, 8:2 and 7:3) or CHI viscosities (20, 100 and 600 mPa·s) using a novel alternating current ES (ACES) process. Such nanofibers were thoroughly characterized by determining physicochemical and nanomechanical properties, along with wettability, absorption capacity and hydrolytic plus enzymatic stability. Furthermore, PCL/CHI nanofiber biological safety was validated in terms of cytocompatibility and hemocompatibility (hemolysis < 2%), in addition to a notable antibacterial performance (bacterial reductions of 99.90% for S. aureus and 99.91% for P. aeruginosa). Lastly, the enhanced wound healing activity of PCL/CHI nanofibers was confirmed thanks to their ability to remarkably promote cell proliferation, which make them ideal candidates for long-term applications such as wound dressings.
Keywords: nanofibers; tissue regeneration; wound healing; polycaprolactone; chitosan; electrospinning